Fungal species and their boundaries matter – Definitions, mechanisms and practical implications. Issue 2 (March 2018) - Steenkamp, Emma T.; Wingfield, Michael J.; McTaggart, Alistair R.; Wingfield, Brenda D.
Abstract: Recent scientific and technological advances have improved and streamlined our ability to recognise and describe fungal species. Detailed comparative genomics studies have also expanded our understanding of species boundaries. Against this background, we explore the nature of fungal species and consider how this impacts our understanding of their genetics and evolution. The current body of evidence suggests that fungal species are unique evolutionary units that are separated from one another by boundaries that are "porous" under certain conditions ("semipermeable" in analogy to the differential permeability of membranes). Overall, the penetrability of these boundaries depends on the relatedness between donor and recipient species, the spatial proximity of related species to one another during their evolution, and the evolutionary potential associated with the breach of a boundary. Furthermore, the semipermeable nature of species boundaries fundamentally affects the population genetics of a species, with potentially profound effects on its overall evolution and biology. This also influences the methodologies used in taxonomy, because some species appear capable of maintaining their genetic isolation despite extensive penetrability of their boundaries. Most analytical procedures are also not able to distinguish the signals of species boundary permeability from those associated with incomplete lineage sorting or intraspecific diversity. Collectively, these issues greatly complicate how we study and name fungi. An awareness of the nature of species, their boundaries and the biological and genomic signatures of boundary breaches, will enhance our ability to identify them and, perhaps more importantly, to develop realistic strategies to manage and manipulate their growth and distribution. Highlights: Under certain conditions fungal species boundaries are permeable. Speciation and barrier genes determine formation of species and their boundaries. Permeability of species boundaries widely impacts the population biology of fungi. The dynamic nature of fungal species influences their taxonomy and control.